Was it Translated: Türkish Diplomatic Correspondence to China in Medieval Times - Lung, Rachel (TTR, 2008)
AbstractAncient diplomatic correspondence to China from East Asian states has been a subject of research interest in Sinology, especially with respect to its relevance to historical politics and ideology in Asia. References to its implications to translation studies, if any, were, however, quite minimal. This article represents an initial attempt to examine China-bound diplomatic correspondence from the perspective of translation history. Diplomatic letters sent in medieval times by Yamato (known as Japan since 700) and the three Korean states (namely, Paekche, Silla, and Koguryǒ) were generally confirmed to be written in Chinese, not translated. However, the case for China-bound diplomatic correspondence from Türk (on Mongolia steppes)—previously a rival state to China, and later on a vassal state—is still controversial. In this article, examples are chosen from two letters presented by the Türkish qaqhans (tribal chieftains) to China during the Sui dynasty (581–618), to find out if these letters might have been translated from the Türkic language into Chinese. Evidence from standard histories of Northern dynasty China (Zhoushu and Beiqishu, among others) suggests the existence and use of a written Türkic language by the mid-sixth century. This written language, borrowing some Sogdian (present-day Uzbek) words, was said to be similar to the other written languages on the steppes, and was found to have been used in diplomatic and religious contexts, as early as the mid-sixth century. This article argues that if there was a written language in Türk at the time, it is reasonable to assume that the Türkish state letters presented to China might have been written in the Türkic language first, before being translated into Chinese.